Synthesis of thermoresponsive oligo(ethylene glycol) polymers through radical ring-opening polymerization of vinylcyclopropane monomers. Issue 4 (13th January 2020) - Stanojkovic, Jovana; Oh, Junki; Khan, Anzar; Stuparu, Mihaiela C.
Abstract : Polyvinylcyclopropanes are designed to exhibit a thermally triggered aggregation process in aqueous solutions. Abstract : Polyvinylcyclopropanes are an old class of polymers typically known for their low polymerization-induced shrinkage properties. In this work, we show that they are capable of exhibiting a thermally triggered aggregation process in aqueous solutions. The phase transition is sharp, tunable within the temperature range of 25–46 °C, and relatively insensitive to environmental conditions. It is anticipated that this preliminary study will shine new light on polyvinylcyclopropanes and lead to new avenues in their studies and future application.